VD_FINDINFO HC / 2014 / 222 vom 24. März 2014 - VD Tribunal cantonal (2014)
NOUVEAU MOYEN DE FAIT, CONCLUSIONS, FARDEAU DE LA PREUVE | 8 CC, 221 al. 1 let. d CPC (CH), 221 al. 2 let. b CPC (CH), 222 al. 2 CPC (CH), 326 al. 1 CPC (CH)